Las infecciones de la mano y su tratamiento - Gret, Luis G. (1938)
He divide the infections hand in to superficial, deep, and osseous for their treatment. In the first category we use «Pneumo Haptinógeno» or staphylo by subcutaneous route giving an ampule daily, or every two or three days according to the evolution of the case. In the second class of cases we use haptinógeno mixed With morphine or novocain injecting it in the same site of the lesion, and if it is necessary we extract previously the excess exudade if there were any, and at the same time making intravenous injection of 20 c.c. of 20 °/0 sodium chloride once or twice daily. In cases of osseous lesions we try staphylo haptinógeno subcutaneously andr if there is no prompt result, we inject it mixed with anaesthetics under the periosteum or as near as possible to the focus of infection.